Analysis of Skill Upgrade, Social Support and Job Characteristics on Employee Performance with Job Satisfaction as A Moderation Variable in Hamparan Perak Health Center - Rini Mutia Pradifta; Yeni Absah; Beby Karina Fawzeea (Journal of Business Management, 2025)
This study analyzes the influence of Skill Upgrade, Social Support, and Job Characteristics on employee performance, with job satisfaction as a moderating variable at Puskesmas Hamparan Perak. Using a quantitative approach, the study involved 100 civil servant samples. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results indicate that Skill Upgrade, Social Support, and Job Characteristics have a positive and significant effect on job satisfaction and employee performance. Job satisfaction mediates the influence of Skill Upgrade, Social Support, and Job Characteristics. This study provides recommendations to enhance employee performance through Skill Upgrade, Social Support, and Job Characteristics.